Cyclic Group 15 Radical Cations1. Issue 25 (8th May 2015) - Brückner, Angelika; Hinz, Alexander; Priebe, Jacqueline B.; Schulz, Axel; Villinger, Alexander
Abstract Singlet cyclo‐1, 3‐dipnicta‐2, 4‐diazane‐1, 3‐diyls of the type [E(μ‐NTer)2E] (2, E=P, As, Ter=2, 6‐dimesitylphenyl) can undergo a one‐electron‐oxidation utilizing silver salts of weakly coordinating anions such as [AgLn][B(C6F5)4] (L=donor solvents) to afford the novel cyclic radical cations, [E(μ‐NTer)2E]+. (3+.). When smaller and more basic anions were employed in the reaction, the anions were found to form covalent bonds to the radical centers yielding dipnictadiazanes, [FP(μ‐NTer)2PF] (5) and [(CF3CO2)P(μ‐NTer)2P(CF3CO2)] (6). A two‐electron oxidation process, resulting in the formation of dications of the type [E(μ‐NTer)2E]2+, could not be observed. Computational and EPR data revealed that the spin density is almost completely localized at the two heavier pnictogen centers E of the former 1, 3‐dipnictadiazane‐1, 3‐diyls. The bonding situation in the radical cations features a rare example of a transannular one‐electron π bond without having a σ bond.